2023
DOI: 10.1186/s13098-022-00966-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-132-3p and KLF7 as novel regulators of aortic stiffening-associated EndMT in type 2 diabetes mellitus

Abstract: Background The prevalence of diabetes mellitus has risen considerably and currently affects more than 422 million people worldwide. Cardiovascular diseases including myocardial infarction and heart failure represent the major cause of death in type 2 diabetes (T2D). Diabetes patients exhibit accelerated aortic stiffening which is an independent predictor of cardiovascular disease and mortality. We recently showed that aortic stiffness precedes hypertension in a mouse model of diabetes (db/db mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…EndMT has also been found to occur in calcific aortic valve disease, where it precedes EC osteogenesis [ 52 , 53 ], and in diabetes-related aortic stiffening [ 35 ]. These instances of EndMT have been shown in both experimental models and in humans [ 35 , 51 , 52 ]. We and others have shown that hyperglycemia-induced EndMT occurs and contributes to DCM both in vitro and in vivo, but these findings have never been recapitulated in human diabetic patients [ 8 , 9 , 16 , 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EndMT has also been found to occur in calcific aortic valve disease, where it precedes EC osteogenesis [ 52 , 53 ], and in diabetes-related aortic stiffening [ 35 ]. These instances of EndMT have been shown in both experimental models and in humans [ 35 , 51 , 52 ]. We and others have shown that hyperglycemia-induced EndMT occurs and contributes to DCM both in vitro and in vivo, but these findings have never been recapitulated in human diabetic patients [ 8 , 9 , 16 , 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDACs 3 and 9 have been shown to induce EndMT in atherosclerotic plaques [ 32 , 33 ], and DNMT1 has been found to promote EndMT in diabetic retinopathy by hypermethylating the lncRNA MEG334. Recently, miR-132-3p—downregulated in diabetes—has been reported to regulate EndMT in the aorta via regulation of Kruppel-like factor 7 [ 35 ]. We have previously identified lncRNA ZFAS1 and miRNAs 9, 146a, and 200b as regulators of fibrosis and EndMT in DCM and other diabetic complications in cell culture and in animal models [ 8 , 9 , 18 , 36 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…RUNX1 [186], hsa-mir-132-3p [606] and HOXA5 [607] was an important therapeutic targets of multiple sclerosis. RUNX1 [81], CAV1 [241], STAT6 [239], CDKN2A [226], SYK (spleen associated tyrosine kinase) [148], hsa-mir-132-3p [608], hsa-mir-10b-5p [609], hsa-mir-155-5p [610], hsa-mir-191-5p [611], SRY (sex determining region Y) [612], PAX2 [613] and PDX1 [614] were the potential molecular targets of the drugs for treating diabetes mellitus. RUNX1 [395], CDKN2A [403], HSPA2 [423], hsa-mir-132-3p [615], hsa-mir-155-5p [610] and USF2 [616] have been reported to be expressed in Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism of some KLFs in diabetes remains unclear ( 44 ), studies have acknowledged the essential role KLFs play in many types of diabetes ( 71 , 89 , 119 124 ) ( Table 3 ). For example, it was reported that KLF7 can regulate insulin sensitivity and susceptibility to type 2 diabetes by lowering adiponectin and leptin levels ( 126 , 127 ), and can negatively regulate miR-132-3p to aggravate the transition of Human Umbilical Vein Endothelial Cells (HUVECs) to a mesenchymal state after high glucose exposure ( 128 ). Similarly, KLF14 has been implicated in increasing susceptibility to type 2 diabetes by regulating key genes associated with insulin resistance ( 122 , 123 ).…”
Section: Klfs and Cardiomyopathymentioning
confidence: 99%